Clinical, Virologic, and Immunologic Characteristics of Zika Virus Infection in a Cohort of US Patients: Prolonged RNA Detection in Whole Blood. (19th December 2018) - El Sahly, Hana M; Gorchakov, Rodion; Lai, Lilin; Natrajan, Muktha S; Patel, Shital M; Atmar, Robert L; Keitel, Wendy A; Hoft, Daniel F; Barrett, Jill; Bailey, Jason; Edupuganti, Srilatha; Raabe, Vanessa; et al.
Abstract: Background: Clinical, virologic, and immunologic characteristics of Zika virus (ZIKV) infections in US patients are poorly defined. Methods: US subjects with suspected ZIKV infection were enrolled. Clinical data and specimens were prospectively collected for ZIKV RNA detection and serologic and cellular assays. Confirmed ZIKV infection (cases) and ZIKV-negative (controls) subjects were compared. Dengue-experienced and dengue-naïve cases were also compared. Results: We enrolled 45 cases and 14 controls. Commonly reported symptoms among cases and controls were maculopapular rash (97.8% and 81.8%), fatigue (86.7% and 81.8%), and arthralgia (82.2% and 54.5%), respectively. The sensitivity (94%) and duration of infection detection (80% positivity at 65–79 days after disease onset) by polymerase chain reaction were highest in whole-blood specimens. ZIKV-neutralizing antibodies had a half-life of 105 days and were significantly higher in dengue virus–experienced cases than naïve ones ( P = .046). In intracellular cytokine staining assays, the ZIKV proteins targeted most often by peripheral blood mononuclear cells from cases were structural proteins C and E for CD4+ T cells and nonstructural proteins NS3, NS5, and NS4B for CD8+ T cells. Conclusions: ZIKV RNA detection was more frequent and prolonged in whole-blood specimens. Immunoglobulin G (IgG) and neutralizing antibodies, but not IgM, were influenced by prior dengue infection. Robust cellular responses to E and nonstructural proteins have potential vaccine development implications.